2023
DOI: 10.1021/acs.jpcc.3c01872
|View full text |Cite
|
Sign up to set email alerts
|

Twin-Graphene: A Promising Anode Material for Lithium-Ion Batteries with Ultrahigh Specific Capacity

Abstract: Lithium-ion batteries have long been the focus of energy storage. The potential application of carbon-derived structures as lithium-ion battery anodes was examined using the first-principles density functional theory approach. The results of our calculations revealed that the modified lattice constant, structure, and parameters are similar to those found in earlier research. It is worth noting that the twin-graphene double layer has several stable adsorption sites for lithium. Meanwhile, we discovered that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…The sample prepared with high ratio of doped graphene oxide (N2) had high initial capacity compared with the other battery since the theoretical capacity of graphene oxide and polypyrrole were 744 mAh g −1 and 72 mAh g −1 , respectively. [76][77][78] In the first cycle, the specific discharge capacity of the battery prepared with N1 anode was 501 mAh g −1 , discharge capacity was 360 mAh g −1 . The first cycle's initial coulombic efficiency (ICE) was approximately 72% for N1 including battery, whereas (N2)'s first coulombic efficiency was around 60%, with discharge and charge specific capacities of 785 and 473 mAh g −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The sample prepared with high ratio of doped graphene oxide (N2) had high initial capacity compared with the other battery since the theoretical capacity of graphene oxide and polypyrrole were 744 mAh g −1 and 72 mAh g −1 , respectively. [76][77][78] In the first cycle, the specific discharge capacity of the battery prepared with N1 anode was 501 mAh g −1 , discharge capacity was 360 mAh g −1 . The first cycle's initial coulombic efficiency (ICE) was approximately 72% for N1 including battery, whereas (N2)'s first coulombic efficiency was around 60%, with discharge and charge specific capacities of 785 and 473 mAh g −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to utilize the effective capacity of the active material. Compared with conductive agents such as commercial conductive agent carbon black (CB), graphene has higher conductivity and specific surface area, and studies have shown that advanced carbon materials, including carbon (one-dimensional) [50], graphene (two-dimensional) [51,52], and 3D graphene backbones (three-dimensional) [53], have been used to build continuous conductive networks for LIBs [54].…”
Section: Graphene As Libs Electrode Conductive Agentmentioning
confidence: 99%
“…The graphene-metal composite material produced by the graphene coating method can, however, improve the electrochemical performance of LIBs [79]. The flexible characteristics of graphene can effectively inhibit the metal electrode volume expansion during the charging and discharging process, and the morphology of graphene can change with changes in the preparation method [52,80,81]. With excellent electrical conductivity, graphene can establish a conductive network between particles, and the high specific surface area can also increase the storage capacity of lithium.…”
Section: Application Of Graphene As Libs Anode Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The K atom is adsorbed at a distance of 2:08 Å from the center of the plane of the triangular hollow of the twin graphene at the A1 site. A more negative value of the adsorption energy E ads ð Þ indicates energetically favorable adsorption, demonstrating that an exothermic reaction between the substrate and K-ion 25,38 occurred during the intercalation process. We have also incorporated the Grimme DFT-D2 vdW correction for higher precision and it is noted that the adsorption energy for K adsorbed at the A1 site to be À1:83 eV with an adsorption height of 1:94 Å from the middle of the plane of the triangular hollow which once again affirms the position as the highest stable site with higher stability.…”
Section: Structural Optimization and Adsorption Energymentioning
confidence: 99%